Mediating effect of felt obligation between perceived organizational support, exemplary leadership practices and organizational citizenship behavior of academic staff - Hassan, Roshafiza (2020)
This study examined the mediating effect of felt obligation on relationships between perceived organizational support, exemplary leadership practices and organizational citizenship behavior of academic staff. As highlighted in the Social Exchange Theory, this study explores academic staff’ felt obligation to reciprocate positive and productive actions when they received favourable treatment demonstrated by leaders and the organizations in the form of organizational citizenship behaviors. This study employed a quantitative descriptive survey whereby a total of 372 academic staff from five Research Universities were selected as samples for the study. A stratified random sampling (proportional) method was applied in the sampling selection. An instrument consisting of 69 items were used to measure academic staff’s perceptions towards their level of organizational citizenship behavior (24-items), perceived organizational support (8-items), exemplary leadership practices (30-items), and felt obligation (7- items) at the workplace. The collected data were analyzed using descriptive statistical tools, such as frequency, percentage, mean, and standard deviation, while seven (7) research hypotheses were formulated and tested using inferential statistical tools, such as Pearson correlation. Structural Equation Modeling (SEM) analysis was employed to test and establish the existence of convergent validity and discriminant validity of the measures. Prior to the utilization of the structural model, the measurement model confirmed the appropriateness of the data was at χ2 (238) = 483.294, p = 0.001, χ2/df = 2.031, GFI = 0.901, TLI = 0.944, CFI = 0.952; IFI = 0.952, RMSEA = 0.053. Thus, the data fit the model. The descriptive analysis revealed that the level of all variables examined in this study were high [organizational citizenship behavior (mean = 5.91, SD = 0.56); exemplary leadership practices (mean = 7.48, SD = 1.67); felt obligation (mean = 6.03, SD = 0.74)] except for the variable of perceived organizational support (mean = 4.80, SD = 1.10) where it was reported as a moderate level. Additionally, the inferential statistical analysis found that none of the demographic variables was significantly related to organizational citizenship behavior. However, based on structural path analysis, it was discovered that all hypotheses were supported. Therefore, the standardized path coefficient showed that the proposed mediational model had a good fit. The goodness of fit indices was summarized as: χ2 (48) = 94.518, p < 0.001, χ2/df = 1.969, AGFI = 0.934; TLI = 0.974, CFI = 0.981; IFI = 0.981, RMSEA = 0.051. Thus, the proposed mediation model was proven fit as RMSEA met the cut-off point 0.051, which appropriately fell between the required ranges of acceptability. Based on this result, this study concluded that perceived organizational support and exemplary leadership practices were confirmed as contextual factors among academic staff that would significantly contribute to their level of citizenship behavior toward the organization they served for. Similarly, through felt obligation, the relationships between perceived organizational support, exemplary leadership practices, and organizational citizenship behavior were mediated among academic staff. Hence, the research model confirmed the theory that academic staff’s organizational citizenship behavior appears to reciprocate with their perception of perceived support by the organizations and exemplary leadership practices by their Heads of Department as well as the influence of their felt obligation. In conclusion, these findings may benefit and can be used by policymakers and administrators to improve the level of perceived support of academic staff and empower leadership practices at the departmental level. Through these improvements, academic staff’s organizational citizenship behavior can be encouraged and their sense of felt obligation can be enhanced in Research Universities, Malaysia.